Ethical dilemmas and legal ambiguity in China: a chain mediation model linking suicide rumination, legitimization, and acceptance among acutely-ill adults - Liu, Guo; Liu, Kai (Frontiers in Psychology, 2024)
Background: This study explores the complex intersection of euthanasia, legal ambiguities, cultural attitudes, and the psychology of suicide among seriously ill patients in China. It addresses the lack of clear legislation on euthanasia and doctor-assisted killing, the impact of cultural and philosophical beliefs, and the evolution of legal and ethical perspectives on suicide. Method: A survey was conducted with 356 Chinese adults, aged 23 to 64 years, using popular social media platforms in China. The study aimed to reflect a broad spectrum of the adult population in terms of age, education, and professional sectors. The research model involves suicide rumination as an independent variable, acutely-ill patients' suicide acceptance as a dependent variable, and three mediators: cognitive depression, ethical suicide acceptance, and suicide legitimization.Results: The findings reveal a significant total effect of Suicide Rumination on Acutely-ill Patients' Suicide Acceptance. The analysis indicates that Suicide Rumination is a significant predictor of Cognitive depression, explaining approximately 8.05% of its variance, However, the effect of Suicide Rumination on Ethical Suicide Acceptance did not emerge as significant, while its impact on Suicide Legitimization was also non-significant. Cognitive depression was found to have a substantial effect in the models for both Ethical Suicide Acceptance and Suicide Legitimization, supporting Hypotheses 3a and 3b. In the comprehensive model assessing Acutely-ill Patients' Suicide Acceptance. Notably, Suicide Rumination, Ethical Suicide Acceptance, and Suicide Legitimization all emerged as significant predictors of this acceptance, with varying effects. The role of Cognitive depression in this model was marginally significant. Crucially, the indirect effects of Suicide Rumination on Acutely-ill Patients' Suicide Acceptance through different mediation paths varied in significance and impact. The indirect effect via Cognitive depression alone, and through the sequential combination of Cognitive depression and Ethical Suicide Acceptance, were significant. These findings underscore the importance of considering multiple pathways in understanding the dynamics of Suicide Rumination and its influence on the acceptance of suicide among acutely-ill patients. Conclusion: This paper presents a comprehensive analysis of the legal, cultural, ethical, and psychological dimensions of euthanasia, doctor-assisted killing, and suicide in China..